Testing the mediating effect of corporate sustainability on the relationship of institutional ownership and firm value - Novita, Dian; Amiruddin, Amiruddin; Sundari, Sri; Ferdiansah, Muhammad Irdam (Edelweiss Applied Science and Technology, 2025)
Corporate sustainability is a concept associated with corporate social responsibility. Corporate social responsibility is a management concept implemented by companies that integrate social and environmental concerns into their business activities and interactions with stakeholders. Corporate sustainability not limited to social and environmental aspects. The disclosure of sustainability reports cannot be separated the implementation of good corporate governance that management framework companies with a broader future agenda. Companies implement good corporate governance able to disclose information of sustainability reports of shareholders. Therefore, when companies implement good corporate governance, the disclosure of sustainability reports will increase, thereby enhancing firm value. This study investigates indirect effect of institutional ownership on firm value through corporate sustainability with audit quality as moderating variable, this use PROCESS Macro Model 15. This analyses financial statements from 2019-2023. The research variables are 728 firm-year observations from publicly listed companies. The data collected from corporate financial statements by accessing corporate websites. Although corporate sustainability mediates the relationship between institutional ownership and firm value, the moderation by audit quality on both the direct and indirect pathways statistically insignificant. These findings highlight the central role of sustainability translating institutional oversight into market value and suggest limited moderating influence of audit quality.